Form and event : principles for an interpretation of the Greek world - Diano, Carlo (Commonalities., 2020)
"Diano's Form and Event has long been known in Europe as a major work not only for classical studies but even more for contemporary philosophy, anticipating the work of Deleuze, Badiou, Esposito, and Agamben. It now appears in English for the first time, with a substantial Introduction that situates the book in the genealogy of modern political philosophy."--